Diagnosis and management of paroxysmal sympathetic hyperactivity: a narrative review of recent literature - Peng Yin; Yunsong Pan; Deshun Chen; Wensheng Dong; Yongjun Fan; Jiaqiu Zhu; Hui Shi (European Journal of Medical Research)
Abstract Paroxysmal sympathoexcitatory syndrome is a clinical syndrome, recognized in a subgroup of survivors of severe acquired brain injury, of simultaneous, paroxysmal transient increases in sympathetic [elevated heart rate, blood pressure, respiratory rate, temperature, sweating] and motor [posturing] activity. Coupled with the absence of uniform treatment guidelines, it is prone to underdiagnosis and misdiagnosis, leading to the adoption of inappropriate treatment protocols, which may adversely affect the prognosis of patients. This narrative review summarized the existing literature and provided a comprehensive account of the research history and terminology of PSH, epidemiology and pathogenesis, diagnostic criteria, therapeutic options, and prognosis, hoping to bring new ideas to the clinical treatment of PSH.